“It all starts with urgency…” Engaging with the local ekklesia of Thessalonica as a window and mirror en route to sustained missionary impact - S. Joubert (Acta Theologica)
Acts 17:1-9 and 1 Thessalonians 1, which form part of the church’s normative library, are two underestimated windows regarding our ecclesiological identity and our missional presence in the world. Both deal with Paul’s effective church planting efforts in the city of Thessalonica. By immersing ourselves in these texts, which also serve as hermeneutical mirrors, we intend to participate in a mimetic learning process, in order to come to terms with the nature of Paul’s embodied proclamation of the Gospel and his missional urgency. This urgency, which was embedded in his own imitation of the suffering and joy of Christ, was also transplanted into the lives of the Thessalonians. In turn, their commitment to the Word, their steadfastness in suffering, and their openness to people from different social strata and cultures turned them into embodied examples of the Gospel right across the Greek world. Hence, the challenge to us as contemporary believers is to creatively, yet urgently, synchronise our own theological agendas, as well as our ecclesial practices and missional activities, with these normative textual mirrors and windows.